2001
DOI: 10.1002/ffj.1040
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity profiles of the two enantiomers of limonene and carvone isolated from the oils of Mentha spicata and Anethum sowa

Abstract: The antimicrobial activity of the essential oils of Mentha spicata L. and Anethum sowa Roxb. (Indian dill) were studied. The major chemical constituents of the hydrodistilled essential oils and their major isolates from cultivated M. spicata and A. sowa were identified by IR, 1 H-and 13 C-NMR and GC: (S)-( )-limonene (27.3%) and (S)-( )-carvone (56.6%) (representing 83.9% of the spearmint oil) and (R)-(C)-limonene (21.4%), dihydrocarvone (5.0%), (R)-(C)-carvone (50.4%) and dillapiole (17.7%) (together 76.9% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
125
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(148 citation statements)
references
References 17 publications
(4 reference statements)
9
125
0
4
Order By: Relevance
“…For example, high content of citral (Paviani et al 2006) was found as the main compound in lemon grass oil, while clove oil contains eugenol, caryophyllene, furfurol, α-pinene and eugenyl acetate and eugenol a phenolic compound (70-90 %) was the main contributor (Matan et al 2006), and the antimicrobial activity of eucalyptus essential oil is due to the presence of a mixture of monoterpenes and oxygenated monoterpenes. (Aggarwal et al 2002). A number of active principles of neem oil are azadirachtin, azadiradione, fraxinellone, nimbinsalannin etc., which could act as the compound for antifungal activity.…”
Section: Effects Of Eos On Colony Diameter Of Test Pathogensmentioning
confidence: 99%
“…For example, high content of citral (Paviani et al 2006) was found as the main compound in lemon grass oil, while clove oil contains eugenol, caryophyllene, furfurol, α-pinene and eugenyl acetate and eugenol a phenolic compound (70-90 %) was the main contributor (Matan et al 2006), and the antimicrobial activity of eucalyptus essential oil is due to the presence of a mixture of monoterpenes and oxygenated monoterpenes. (Aggarwal et al 2002). A number of active principles of neem oil are azadirachtin, azadiradione, fraxinellone, nimbinsalannin etc., which could act as the compound for antifungal activity.…”
Section: Effects Of Eos On Colony Diameter Of Test Pathogensmentioning
confidence: 99%
“…Spearmint essential oils are used in the food and pharmaceutical industries and are found in various consumer products including chewing gum, toothpaste, mouthwashes, as well as in pharmaceuticals, confectionary, and aromatherapy (Mint Industry Research Council, 2009). Both whole essential oils and individual essential oil constituents such as (-)-carvone have antimicrobial properties (Aggarwal et al, 2002;de Carvalho and Da Fonseca, 2006;Chao et al, 2000;Kanatt et al, 2008;Rafi i and Shahverdi, 2007;Rasooli et al, 2009;Sivropoulou et al, 1995;Sokovic et al, 2009).Th e midwestern and northwestern United States are considered ideal for spearmint production (USDA-NASS, 2009). In 2008, the United States produced 1.09 million kg of spearmint oil, and the average essential oil yields for the same year were 132 kg/ha (USDA-NASS, 2009).…”
mentioning
confidence: 99%
“…However, studies performed with other terpenes have also indicated greater antimicrobial effect of dextrorotatory isomers. Aggarwal et al (2002) demonstrated that (R)-(+)-limonene and (R)-(+)-carvone are the most potent isomers against bacteria and dermatophytic fungi. In other studies, only the dextrorotatory enantiomers of α-and β-pinene were active against Candida albicans, Cryptococcus neoformans, Rhizopus oryzae and methicillin-resistant Staphylococcus aureus (Silva et al 2012b).…”
Section: Discussionmentioning
confidence: 99%